Antioxidant properties of white tea in (pre)diabetic rats - Silveira, Ana Carolina Lourenço (2018)
Diabetes Mellitus (DM) is one of the most prevalent metabolic diseases in the western world and results from failure of insulin secretion and/or action. This hormone, produced in pancreatic ß cells allows cells to capture glucose to meet their energy needs. When insulin is absent or when its function is not normal the cells do not absorb glucose that remains in the bloodstream causing hyperglycaemia. DM is associated with excessive formation of free radicals and when endogenous antioxidant defenses are not present in sufficient amounts to neutralize them cause cell damage. DM is associated with excessive free radical formation and when endogenous antioxidant defenses are not present in sufficient amounts to neutralize them, they cause cell damage. DM is still associated with aging and with age progression there is a tendency for several complications to arise in different organs. One of the complications that occurs later is respiratory failure resulting from physiological and structural changes in lung tissue and decreasing alveolar gas exchange. Prediabetes (PrDM) is a condition in which some, but not all, of the criteria for DM are verified and represent a high risk for the development of DM and whose prevalence has been increasing significantly in recent decades. It is therefore essential to find therapeutic alternatives in the fight against the negative effects of this pathology and its progression to DM. White tea is rich in polyphenols and methylxanthines, which is why it has a high antidiabetic and antioxidant potential. This study intends to evaluate for the first time the effects of PrDM in the lung and to verify if the regular consumption of white tea contributes to the improvement of the antioxidant capacity of the lung tissue of PrDM rats. A Wistar rat model with PrDM induced with a low dose of streptozotocin was used in which one of the groups consumption of water was replaced by white tea. After two months the lung tissue was collected and the antioxidant potential, the activities of seceral enzymes involved in the endogenous antioxidant defenses and some oxidative parameters, such as protein oxidation (nitration and carbonylation), lipid peroxidation and damage in the deoxyribonucleic acid. In this study, PrDM was found to decrease the activity of the superoxide dismutase and glutathione peroxidase. In addition, it increased levels of protein nitration and lipid peroxidation and decreased histone H2A levels of this tissue. That is, with the decrease in the activity of antioxidant enzymes of the lung occurred an increase in the oxidative damage of its cells. Our results demonstrate that regular consumption of white tea restored the total antioxidant capacity of lung tissue, decreased levels of protein nitration and lipid peroxidation, and increased levels of histone H2A from this tissue. These results show for the first time that regular consumption of white tea improves the antioxidant capacity of the lung tissue of PrDM rats, suggesting that it may be a natural and economical alternative to treat the deleterious effects of PrDM in the lung and avoid progression to DM.